The Oral Contraceptive Pill and Adolescents' Mental Health - Ana Costa-Ramón; N. Meltem Daysal; Ana Rodríguez-González (Center for Economic Studies and ifo Institute (CESifo), 2023)
What is the impact of the oral contraceptive pill on the mental health of adolescent girls? Using administrative data from Denmark and exploiting the variation in the timing of pill initiation in an event study design, we find that the likelihood of a depression diagnosis and antidepressant use increases shortly after pill initiation. We then uncover substantial variation in primary care providers' tendency to prescribe the pill to adolescents, unrelated to patient characteristics. Being assigned to a high prescribing physician strongly predicts pill use by age 16 and leads to worse mental health outcomes between ages 16-18.
Keywords: I12; J13; 330; contraceptive pill; mental health; adolescents; prescribing practices